2023
DOI: 10.1021/acsomega.2c06550
|View full text |Cite
|
Sign up to set email alerts
|

Comparison on Quality Performance of Human Hair Types with Herbal Oils (Grape Seed/Safflower Seed/Rosehip) by Analysis Techniques

Abstract: Hair is exposed to harmful factors such as sunlight, pollution, cosmetic applications, and cleaning every day. With lost moisture, the hair is worn out, loses shine, and exhibits color changes in the case of dyed hair. In this study, the effects of herbal oils on hair were investigated by comparing the properties with measurements. Three different types of hair were used: natural (unprocessed), damaged, and dyed hair. After washing hair with a base shampoo, herbal oils were applied, and brightness, color chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that plant extracts can help delay the photoaging of hair. In a study on hair repair using vegetable oil, it was found that grape seed oil has the highest glossiness, and based on color changes, safflower seed oil has the best glossiness effect [ 30 ]. All samples were subjected to tensile strain tests and rose fruit oil showed the best effect.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that plant extracts can help delay the photoaging of hair. In a study on hair repair using vegetable oil, it was found that grape seed oil has the highest glossiness, and based on color changes, safflower seed oil has the best glossiness effect [ 30 ]. All samples were subjected to tensile strain tests and rose fruit oil showed the best effect.…”
Section: Discussionmentioning
confidence: 99%